Physical activity and wellbeing of 8–9 year old children from social disadvantage: An all-Ireland approach to health. (October 2017) - Breslin, Gavin; Fitzpatrick, Ben; Brennan, Deidre; Shannon, Stephen; Rafferty, Ruth; O'Brien, Wesley; Belton, Sarahjane; Chambers, Fiona; Haughey, Tandy; McCullagh, Darryl; Gormley, Richard; Hanna, Donncha
Abstract: Background: Physical activity (PA) has been shown to improve psychological wellbeing in adults, however less is known about this relationship in children. The aim of this study was to examine the relationship between PA and wellbeing in children for the first time across Ireland and to explore potential differences by gender, jurisdiction (Northern Ireland and the Republic of Ireland) and region of Ireland. Method: A sample of 673 8–9 year olds attending school in socially disadvantaged areas took part. Participants completed a measure of PA and the KIDSCREEN-27 quality of life questionnaire. Results: 18% of children accumulated the recommended 60 min of MVPA per day for health, with 18% of boys (n = 63) and 17% girls (n = 55) achieving this level. Children in Northern Ireland reported higher wellbeing scores than those in Republic of Ireland. Children achieving the recommended level of MVPA scored significantly higher on measures of wellbeing than less active children. Gender differences in wellbeing were found for perceived parental, social and school support with girls scoring higher than boys. Conclusions: Children who meet the recommended MVPA guidelines and those who live in Northern Ireland report a higher level of wellbeing than their peers who live in the Republic of Ireland. Highlights: The first examination of physical activity and wellbeing in socially deprived children across the island of Ireland. There is a significant, positive relationship between wellbeing and physical activity. Irish girls report significantly higher perceived wellbeing than boys. Irish boys and girls take part in equally low amounts of Physical Activity.